PENGARUH CUSTOMER EXPERIENCE TERHADAP CUSTOMER SATISFACTION PADA PENGGUNA SMARTPHONE ANDROID ( Studi pada Mahasiswa Politeknik Negeri Banjarmasin) - Ronny Mantala; Muhammad Riza Firdaus (Universitas Lambung Mangkurat, 2016)
Android smartphones are the cellular products that currently become phenomenal and popular among students. The customers’ experiences and the influence on the users’ satisfactions are interesting topics to be investigated. This research was conducted to investigate and to analyze the influence of customers’ experience dimensions, such as: users’sensing, feeling, thinking, acting and relation by their satisfaction, both simultaneously and partially on the students of Politeknik Negeri Banjarmasin. Nonprobability sampling method was used through purposive method sampling for 60 samples. The hypothesis was tested through doubled linear regression analysis. The first tested hypothesis results were found that the independentvariables of customers’ experience, such as: sensing, feeling, thinking, acting, and relation which directly influenced their satisfaction among students as the users. The second tested hypothesis results showed that only three variables of customer experience (sensing, thinking, and relation) that significantly influenced the customers’satisfaction; furthermore, the feeling and acting variables did not directly influence customers’satisfaction significantly. These results also showed that the relation variable dominantly contributed to customers’ satisfaction partially if this variable was compared with other variables (sensing, feeling, thinking and acting).